Traits of psychoanalysis “in two figures from Machado de Assis” - Passos, Cleusa Rios P. (Estudos Avançados, 2023)
This essay is a tribute to Alfredo Bosi and his vast work and contribution to literature and Brazilian culture. The focus is “Uma figura machadiana”, the article in which he analyzes Memorial de Aires, drawing on psychoanalysis, among other sources. The proposed reading emphasizes the role of these knowledge sources in the novel by Machado de Assis, and tries to redeem it as he follows and pursues certain ideas, always considering the force of the psychoanalytic trait in the construction of the text.